Drinking Water Hardness (as a Proxy for Calcium) Significantly Modifies the Relationship Between Dental Caries Prevalence in 5 Year Old Children and Drinking Water Fluoride and Socio-economic Inequalities in England - Mohammad Mehrabi; Yang Han; Deborah Moore; Matthew J. Ascott; Anne-Marie Glenny; David A. Polya (Exposure and Health, 2026)
Dental caries (DC) is the most prevalent chronic disease. Previous studies have revealed negative associations between DC prevalence and both drinking water fluoride concentration (F) and socioeconomic status but further predictors, notably drinking water calcium, have been little explored, particularly in the UK. Therefore, this study employed multiple linear regression (MLR) to model the dependency of children’s DC on all three of these predictors, namely (i) F, (ii) IMD: index of multiple deprivation, and (iii) WH: water hardness—as a proxy for calcium concentration; in England. The results showed that all three predictors are statistically significantly (p < 0.05) associated with DC, with, separately, increased fluoride, increased water hardness, and decreased deprivation being associated with lower DC. A key novel finding is that the DC ~ F relationship is quantitatively less pronounced (by about 24%) when WH is included as a predictor—thus the oral health and financial benefits of water fluoridation based on models not considering water calcium may overestimate or underestimate those benefits depending upon water calcium (or WH as a proxy). Moreover, segmented analyses showed that, potentially and partially due to WH’s influence, the DC ~ F relationship is dependent upon F concentration, with the dependence much stronger for drinking water F < 0.10 mg/L than for F > 0.37 mg/L, a concentration considerably lower than the widely reported optimal F, i.e., (0.7–1.0) mg/L. Any modelling of expected costs and benefits for fluoridation should explicitly include consideration of water calcium (or WH as proxy) and the non-first-order linear DC ~ F relationship.